VD_FINDINFO HC / 2014 / 503 vom 1. Juli 2014 - VD Tribunal cantonal (2014)
TRANSACTION JUDICIAIRE, PROTECTION DE L'UNION CONJUGALE | 105 al. 1 CPC (CH), 109 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH)